2017
DOI: 10.1101/112904
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zika viruses encode multiple upstream open reading frames in the 5′ viral region with a role in neurotropism

Abstract: 14 Zika virus is a single-stranded, positive-sense RNA virus of the family Flaviviridae, which has 15 recently undergone a rapid expansion among humans in the Western Hemisphere. Here, we report 16 a high-resolution map of ribosomal occupancy of the Zika virus genome during infection of 17 mammalian and insect cells, obtained by ribosome profiling. In contrast to some other flaviviruses 18 such as West Nile, we find no evidence for substantial frameshift-induced ribosomal drop-off 19 during translation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
(29 reference statements)
0
3
0
1
Order By: Relevance
“…While the functional significance of the putative peptide remains unknown, a close overlap of uORF stop codon (100 th nt) with main ORF's start codon (96 th nt, Fig.4C) could directly impact ribosome loading and usage rates-key parameters in regulating protein synthesis [50]. Although a canonical structure of 5 UTR is shared amongst flaviviruses [51], this strategy of translation initiation might suggest the enhanced translational efficiency of JEV and ZIKV [13] over DENV [9]. This site exhibits high conservation across JEV strains with the exception of vaccine strain (SA14-14-2) harbouring a silent mutation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the functional significance of the putative peptide remains unknown, a close overlap of uORF stop codon (100 th nt) with main ORF's start codon (96 th nt, Fig.4C) could directly impact ribosome loading and usage rates-key parameters in regulating protein synthesis [50]. Although a canonical structure of 5 UTR is shared amongst flaviviruses [51], this strategy of translation initiation might suggest the enhanced translational efficiency of JEV and ZIKV [13] over DENV [9]. This site exhibits high conservation across JEV strains with the exception of vaccine strain (SA14-14-2) harbouring a silent mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The putative uORF would generate a 22 a.a long peptide (LRRIERLVQFKQFFRTEDNHD) with a termination codon immediately downstream of canonical start codon (Fig.4C). A recent study on riboprofile of ZIKV also showed ribosomal initiation scanning from out-of-frame non-canonical start codons present in the 5 UTR -CUG (uORF1) and UUG (uORF2) [13].…”
Section: Translation Of Upstream Orf In 5 Utrmentioning
confidence: 94%
See 1 more Smart Citation
“…寨卡病毒属黄病毒属、黄病毒科 [19,20] , 是一种单链 核糖核酸(RNA)虫媒病毒, 并具有十二面体结构 [21,22] . 由甲基转移酶和 RNA 聚合酶组成的多功能蛋白(NS5) 是一种在寨卡病毒复制过程中起重要作用的蛋白组分, 它由甲基转移酶(5M5B)和 C-末端 RNA 依赖性 RNA 聚 合酶(RDRP)组成 [23] .…”
unclassified